Cellulase Production by a Locally Isolated Fungal Strain Grown on Oil Palm Empty Fruit Bunch - Samsu Baharuddin, Azhari (2006)
The bioconversion of a local lignocellulosic material, i.e, oil palm empty fruit bunch (OPEFB) was studied in 250 ml Erlenmeyer flasks and locally designed rotary drum and tray cabinet bioreactors. The aim of this study is to utilize the OPEFB for the production of cellulolytic enzymes and sugars, as it offers an enormous economic potential for the bioconversion of agro-industrial residues generally regarded as waste. Bioconversion profiles suggest that the cellulolytic enzymes production from OPEFB in solid substrate fermentation (SSF) was better when using mono culture than co-culture condition with locally isolated fungal strains (Aspergillus niger EB4 and Trichoderma sp EB5). A. niger EB4 produced the highest cellulolytic enzymes activity (FPase 4.3 U/g, CMCase 8.2 U/g, β-glucosidase 19.1 U/g) at day 7 fermentation with carboxymethylcellulose (CMC) as pre-culture cellulase inducer. Soluble protein and reducing sugars were determined to evaluate fungal growth and substrate uptake in the SSF by the fungal strains. Scanning electron microscopy (SEM) showed the capability of these local fungal strains in mono and co-culture conditions for OPEFB degradation. The bioconversion of pre-treated OPEFB for cellulolytic enzymes production by A. niger EB4 was successfully achieved in tray cabinet bioreactor (static condition, without forced aeration) which mimicked SSF conditions in flasks experiment. It is possible to obtain 3.2 ± 0.26, 6.3 ± 0.38, 19.0 ± 0.85 U/g enzyme activity of FPase, CMCase, and β-glucosidase respectively after 6 days fermentation. The extracted crude enzyme from tray cabinet bioreactor experiment was partially purified using ammonium sulphate precipitation. The results showed that protein fraction at 80% ammonium sulphate saturation had managed to precipitate the cellulolytic enzymes with recoveries of 8.1% (2.1 fold), 7.7% (2.0 fold) and 5.8% (1.5 fold) for β-glucosidase, CMCase and FPase respectively. The molecular weights of precipitated cellulolytic enzymes were estimated to be 67 and 120 kDa using SDS-PAGE analysis. The results of saccharification for 5% (w/v) pre-treated OPEFB using enzymatic hydrolysis suggest that the reducing sugars production was significantly affected by the concentration of enzymes and its purity. The use of precipitated cellullases at 3% (v/v) enzyme concentration (6 ml/g substrate) of A.niger EB4 successfully hydrolyze pre-treated OPEFB to produce 7.7 g/l of reducing sugars which corresponds to 27.8% conversion (55.3% cellulose fraction). Due to its rich organic nature, OPEFB can serve as a potential and feasible substrate for microbial process in the production of value added products such as cellulolytic enzymes and sugars.